Concepts in solids : lectures on the theory of solids - Anderson, P. W. (Philip W.), 1923-2020 (World Scientific, 1997)
These lecture notes constitute a course on a number of central concepts of solid state physics - classification of solids, band theory, the developments in one-electron band theory in the presence of perturbation, effective Hamiltonian theory, elementary excitations and the various types of collective elementary excitation (excitons, spin waves and phonons), the Fermi liquid, ferromagnetic spin waves, antiferromagnetic spin waves and the theory of broken symmetry. The book can be used in conjunction with a survey course in solid state physics, or as the basis of a first graduate-level course. It can be read by anyone who has had basic grounding in quantum mechanics.